2011
DOI: 10.1007/s10198-011-0307-1
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime costs of the top five cancers in Taiwan

Abstract: The purpose of this study was to determine cancer-related medical care costs for long-term cancer care costs of breast, cervical, liver, lung, and colorectal cancer. Data were sourced from Taipei Veterans General Hospital cancer registry and claim data during 1999-2002. Besides, claimed data from National Health Insurance were used to match the comparison group. To estimate lifetime cost (10 years), the whole disease process was divided into initial, continuing, and terminal three phases. The expected lifetime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
(25 reference statements)
1
13
0
Order By: Relevance
“…Patients with poor prognosis showed a higher suicide risk in our study, which is consistent with previous studies . In Taiwan, cancers such as the lung, liver, pancreas, and esophagus are cancers with poor prognosis and they also come with higher initial and average medical expenditure, which may lead to hopelessness; and hopelessness is strongly associated with suicidal risks in patients with cancer . Head and neck, esophageal, and lung cancers in male patients were associated with higher suicide risks, similar to the result from the United States, with the nasopharyngeal cancer having the highest risk for suicide in the female patients in Taiwan.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Patients with poor prognosis showed a higher suicide risk in our study, which is consistent with previous studies . In Taiwan, cancers such as the lung, liver, pancreas, and esophagus are cancers with poor prognosis and they also come with higher initial and average medical expenditure, which may lead to hopelessness; and hopelessness is strongly associated with suicidal risks in patients with cancer . Head and neck, esophageal, and lung cancers in male patients were associated with higher suicide risks, similar to the result from the United States, with the nasopharyngeal cancer having the highest risk for suicide in the female patients in Taiwan.…”
Section: Discussionsupporting
confidence: 90%
“…In Taiwan, the health care expenditure for patients with newly diagnosed cancer is high within the first year, with it hitting the highest in the first month after diagnosis and then drops rapidly until month 6, followed by a plateau to the end of second year . Medical expenditures are also higher for survivors with cancer diagnosis within 1 year than that thereafter in the United States .…”
Section: Discussionmentioning
confidence: 99%
“…Our estimate of lifetime cost to the NHI also corroborates with another study using claims data from a single tertiary care medical centre in Taiwan during 1999e2002; the undiscounted average cost up to 10 years for lung cancer was NT$ 448 371 (1US$ ¼ NT$ 33 in 2002), which is equivalent to US$16 703 in 2010. 10 Thus, we tentatively concluded that the two datasets, TCR and NHIRD, and the method used in this study are valid. The resulting estimates may be useful in future health policy decisions, especially regarding cancer prevention programmes.…”
Section: Discussionmentioning
confidence: 59%
“…[4] A study ever showed that the average lifetime costs (10 years) for cervical cancer were NT$511,563 in Taiwan (in 2012 NTD, 1USD≠NTD 33). [5] …”
Section: Introductionmentioning
confidence: 99%